2023
DOI: 10.21203/rs.3.rs-2422049/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of peer-assisted teaching of medical English skills to nonnative English-speaking medical students

Abstract: Background Peer-assisted learning has been shown to be constructive in numerous aspects of undergraduate medical education. The purpose of this study was to evaluate the effectiveness of peer-assisted teaching of medical English skills to nonnative English-speaking medical students. Methods A medical English conversation course was conducted by a group of medical students (i.e. peer-teachers), and targeted participants were intermediate level fellow students from the same program. A longitudinal study was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The aim of this project was to evaluate the effectiveness of peer-assisted teaching of medical English skills to non-native English-speaking students from the Clinical Sciences program at the Faculty of Medicine, Damascus University. An earlier version of this study can be found on ResearchSquare 16 .…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this project was to evaluate the effectiveness of peer-assisted teaching of medical English skills to non-native English-speaking students from the Clinical Sciences program at the Faculty of Medicine, Damascus University. An earlier version of this study can be found on ResearchSquare 16 .…”
Section: Introductionmentioning
confidence: 99%